PEDAGOGICAL CONDITIONS FOR PREPARING CHILDREN FOR SOCIAL LIFE IN SINGLE-PARENT FAMILIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article is devoted to the study of the content and socio-pedagogical features of preparing children from single-parent families for social life, the idea is discussed that a clear definition of pedagogical activities aimed at preparing children for social life allows substantiating the significance of the proposed methodological ideas.